2021
DOI: 10.1007/s41981-021-00154-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a 3D-printed tubular reactor for free radical polymerization by CFD

Abstract: A flow reactor for the complex reaction network of the free radical solution polymerization of n-butyl acrylate was optimized by a combination of kinetic modeling, computational fluid dynamics (CFD) and additive manufacturing. CFD was used to model a flow reactor with SMX mixing elements. An optimized geometry was 3D-printed from polypropylene. The modeled residence time behavior was compared to relevant experiments, giving a validation for the flow behavior of the reactor. A kinetic model for the free radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The same reaction‐ware can be printed with the same printer from polypropylene if higher chemical and thermal stability is needed. 11…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The same reaction‐ware can be printed with the same printer from polypropylene if higher chemical and thermal stability is needed. 11…”
Section: Resultsmentioning
confidence: 99%
“…The same reactionware can be printed with the same printer from polypropylene if higher chemical and thermal stability is needed. [11] Once an optimized reactor geometry/design is found, the CAD drawings can be used to directly manufacture a metal reactor, e.g., also by additive manufacturing. This can give access to reactors more suitable for isothermal behavior.…”
Section: D Printing Of the Reactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values have already been used in combination with CFD simulations for the development of a flux reactor, which provided good agreements with the experiment. [ 29 ] The kinetic model includes the usual initiation, propagation, transfers and termination by recombination as well as disproportionation reactions. It was demonstrated that correct description of chain length and monomer conversion dependence during bulk radical polymerization is essential to model them successfully.…”
Section: Modellingmentioning
confidence: 99%
“…The use of dimensionless numbers (𝑅𝑒, 𝑅𝑒 𝑜 , 𝑆𝑡, 𝐷𝑒 𝑜 ) has helped in the design and development of high-efficiency reactors [33][34][35][36][37]. Computational Fluid Dynamics (CFD), CFD-led explorations have been extensively carried out for improving the design of reactors, where design improvements can be identified based on visualisations of the flows [38][39][40]. However, these are expensive and are often based on human intuition of the parameter space, which makes this approach ineffective at balancing the number of evaluations needed to identify truly optimal solutions.…”
Section: Introductionmentioning
confidence: 99%